Zvonovi za topove - Ambrožič, Matjaž (Acta ecclesiastica Sloveniae, 2024)
From the Middle Ages, bell-makers were frequently transformed into cannon casters. In the past, bells in our lands suffered much due to Ottoman invasions, and most of all during the time of both World Wars. When requisitioning bronze bells, the Austro-Hungarian authorities cited war conditions. They took into consideration artistically and historically important bells, the fate of which was to be decided by the monument preservation service. In 1915/1916, in agreement with the Ministry of Defence, the land authorities instructed diocesan ordinariates to make an inventory of bells throughout parishes according to a special form. In the summer of 1916, priests and believers wrote copious requests to ordinariates or bishops to intervene with the military authorities for the preservation of individual bells. They were also supported by some mayors and, in places, petitions were also signed by people from church communities. Prior to the second requisitioning of bells, which started in August 1917, the military command again asked ordinariates for help during the action. Priests had two weeks to present lists of the remaining bells. Only those bells cast prior to 1600 were exempt from requisition, while others escaped confiscation due to having extraordinary ornamental and figural decoration. Every church with regular pastoral care was to retain at least one bell. Generally, only those bells were left that were marked by the conservator. In Slovenia, only a very small number of original bells from prior to 1916 were preserved, since during both requisitions 90% of all bells were requisitioned. After the First World War, the Kingdom of Italy received war indemnity from Austria from which it financed the casting of the so-called compensation bells on the newly acquired Slovenian territory. In the years after the First World War, emptied bell towers in the Slovenian lands which were made part of the Kingdom of SCS were filled with bronze and steel bells. They were mostly cast by local bell foundries. On 23 April 1942, the Italian Fascist authority decided that bells from churches in Primorska and Istria be requisitioned for military purposes. Mostly, this was the requisitioning of compensation bells. Even some that had been exempted by Austro-Hungary or those returned from the Austrian collection centres after the First World War were now listed for requisition. In the territory of the so-called Ljubljanska pokrajina, Italians did not requisition bronze bells, similarly as the Hungarians in Prekmurje. The German occupier caused the most damage by requisitioning bronze bells primarily from churches in Štajerska and Zasavje and Posavje and to date that damage has not been repaired. Between 1941 and 1944, only those bronze bells were not requisitioned which were protected by the Austrian preservation service during the First World War; however, in Zasavje and Posavje, where the Slovenian population was forced out, almost all historical bells were requisitioned. Only bronze bells in certain churches in the Zgornja Savinjska, Šaleška, and Mežiška valleys were left untouched. In Gorenjska, bronze bells were preserved thanks to the master organist Franc Jenko. The Yugoslav Communist authorities demanded war indemnity from Italy. The Italian government paid 120,000,000 lira of compensation. Unfortunately, the demands of the Yugoslav authorities for the return of unmelted bells from Austria for Styrian parishes were not successful. Bells from the Kočevje region from demolished churches were destroyed or got a new home in bell towers of some nearby churches. Many went to bell towers near Laško.
Keywords: bells; druga svetovna vojna; First World War; prva svetovna vojna; rekvizicija zvonov; requisition of bells; Second World War; zvonovi